Nghiên cứu chế tạo, cấu trúc và tính chất của nanocompozit trên cơ sở cao su thiên nhiên và silica biến tính.Phần II - Ảnh hưởng của chất hoạt động bề mặt đến cấu trúc và quá trình lưu hóa của nanocompozit. - Hưng, Đặng Việt; Chương, Bùi; Minh Ngọc, Phan Thị; Lánh, Phạm Thị; Cường, Trần Việt; Nam, Hoàng (Vietnam Journal of Chemistry, 2014)
Effects of surfactant content on the morphology of silica reinforced natural rubber nanocomposite were investigated. With sufficient amount of surfactant, aqueous silica suspension maintains its stability and silica were distributed in aggregate of 3-10 primary particles in rubber matrix. Effect of silica content on was also studied. Fine distribution of silica particles in range of 30 - 100 nm were observed with silica content up to 40 phr. After latex coagulation, silica particle size was reduced approximately ten times. Master batch of silica/rubber nanocomposite of 40 phr silica were prepared.